A review on potential use of coal bottom ash as a supplementary cementing material in sustainable concrete construction - Mangi, Sajjad Ali; Mohd Haziman, Wan Ibrahim; Norwati, Jamaluddin; Mohd Fadzil, Arshad; Memon, Fareed Ahmed; Putra Jaya, Ramadhansyah; Shahiron, Shahidan (Penerbit UTHM, 2018)
The demand of concrete is increased rapidly due to worldwide growth in infrastructural development. Consequently, consumption of concrete also raises the demand for Portland cement, because it is the fundamental material in concrete construction. The increasing demand for Portland cement is expected to be encountered by introducing new supplementary cementing materials. Considering the sustainability of construction, it is imperative to develop supplementary cementing materials from the industrial waste by-products; one of such waste is the coal bottom ash, produced by coal-based thermal power plants. Previously several studies have been conducted on the utilization of coal bottom ash in its original form as natural sand replacement but limited research has been reported on the coal bottom ash as replacement of cement. It was observed through the literature review that the original coal bottom ash is porous in nature, and cannot be used as a replacement of cement, but after the proper grinding, it possesses the good pozzolanic property and could be utilized as replacement of cement in concrete. The result of this review has indicated that ground coal bottom ash has a good potential to be utilized as supplementary cementing materials in concrete construction. The aim of this review is to summarize the previous findings on the utilization of coal bottom ash as supplementary cementing materials in concrete construction. Hence, this article will deliver the key information and valuable material for the researchers looking for the supplementary cementing materials in the field of advanced concrete technology.